PENGEMBANGAN MEDIA MEMBACA KARPACA UNTUK MENINGKATKAN KEMAMPUAN MEMBACA SISWA KELAS 1 SEKOLAH DASAR - Puji, Puji Rahayu Ningsih; Kusumaningrum, Diana (Universitas Islam Raden Rahmat Malang, 2023)
This research was conducted according to the background, namely the discontinuity between the government's prohibition on reading tests for prospective new students in grade 1 SD and the existing competence test at the grade 1 SD level, there was no media or starting reading material at the grade 1 SD level, learning had not been completed. letter recognition at the kindergarten level due to the Covid-19 pandemic. This research aims to produce reading media that is valid, appropriate and can improve the reading ability of 1st grade students. The development research model used is the Borg and Gall model which has been simplified into 7 research steps namely 1) research and initial information gathering, 2) planning, 3) initial product format development, 4) validation, 5) product revision, 6) trial small scale product, 7) final product revision. Based on the results of the material expert's assessment, a percentage score of 89% was obtained in the valid category. The percentage by media experts is 93% with a very valid category. The feasibility of the media is shown by a teacher user review questionnaire of 92% with a very decent category. The attractiveness of the media is shown by the results of the student response questionnaire of 100% in the very interesting category. An increase in reading ability is shown by a comparison of the results of the pre-test score of 48.52 and the acquisition of the post-test score of 84.80. The results of the gain test (N-Gain) show an index of 0.7 which is included in the high category, so that KARPACA reading media can improve the reading ability of 1st grade students.